(untitled) (Revista da Faculdade de Medicina Veterinária e Zootecnia da Universidade de São Paulo, 1976)
The electrocardiographic patterns of dogs which had its sinus node both partially or totally removed by surgical methods were obtained. Electrocardiograms were taken before, during and after the surgery employing standard, unipolar, chest, epicardic atrial and intracavitary (atrial) unipolar leads. Twelve electrocardiographic changes were characterized and could be correlated with partial or total sinus node removal. These studies provide evidence for a hierarquic competence of this tissue, even though altered as compared, to other components involved in the conduction of the cardiac stimulus.